Nonsyndromic cleft palate: An association study at GWAS candidate loci in a multiethnic sample. Issue 10 (2nd March 2018) - Ishorst, Nina; Francheschelli, Paola; Böhmer, Anne C.; Khan, Mohammad Faisal J.; Heilmann‐Heimbach, Stefanie; Fricker, Nadine; Little, Julian; Steegers‐Theunissen, Regine P.M.; Peterlin, Borut; Nowak, Stefanie; Martini, Markus; Kruse, Teresa; et al.
Abstract : Background: Nonsyndromic cleft palate only (nsCPO) is a common and multifactorial form of orofacial clefting. In contrast to successes achieved for the other common form of orofacial clefting, that is, nonsyndromic cleft lip with/without cleft palate (nsCL/P), genome wide association studies (GWAS) of nsCPO have identified only one genome wide significant locus. Aim of the present study was to investigate whether common variants contribute to nsCPO and, if so, to identify novel risk loci. Methods: We genotyped 33 SNPs at 27 candidate loci from 2 previously published nsCPO GWAS in an independent multiethnic sample. It included: (i) a family‐based sample of European ancestry ( n = 212); and (ii) two case/control samples of Central European ( n = 94/339) and Arabian ancestry ( n = 38/231), respectively. A separate association analysis was performed for each genotyped dataset, and meta‐analyses were performed. Results: After association analysis and meta‐analyses, none of the 33 SNPs showed genome‐wide significance. Two variants showed nominally significant association in the imputed GWAS dataset and exhibited a further decrease in p ‐value in a European and an overall meta‐analysis including imputed GWAS data, respectively (rs395572: PMetaEU = 3.16 × 10 −4 ; rs6809420: PMetaAll = 2.80 × 10 −4 ). Conclusion: Our findings suggest that there is a limited contribution of common variants to nsCPO. However, the individual effect sizes might be too small for detection of further associations in the present sample sizes. Rare variants may play a more substantial role in nsCPO than in nsCL/P, for which GWAS of smaller sample sizes have identified genome‐wide significant loci. Whole‐exome/genome sequencing studies of nsCPO are now warranted.